Factors associated with adherence to pharmacological treatment among elderly persons using antihypertensive drugs - Aquino,Glenda de Almeida (2017)
Abstract Objective: analyze adherence to pharmacotherapy and associated factors among elderly patients using at least one antihypertensive medication. Methods: A cross-sectional, population-based study was performed of elderly patients resident in Juiz de Fora, Minas Gerais, Brazil. Adherence to medication was assessed with the Morisky-Green Test. Socio-demographic variables and variables related to health status, the health service and drug therapy were collected. The Poisson regression model was used to assess crude and adjusted (95% confidence interval) prevalence ratios (PR). The level of significance was tested using the Wald test. Results: The prevalence of adherence to pharmacological therapy was 47% (95% CI: 41%-53%). The sample consisted of 279 elderly persons, the majority of whom were women (69%), described themselves as white (45.5%), and had up to four years of schooling (76.48%). Regarding pharmacological therapy, the subjects took 5.19 (±2.8) medications and 7.1 (±4.4) tablets per day. Conclusion: a significant association was observed between adherence to pharmacological therapy and the variables positive perception of vision, positive perception of hearing and absence of frailty.